Предмет: Алгебра,
автор: THE1DEVILL
(2х-3)(2х+3)-х2=12х-69+3х2 Подскажите как решать)
Ответы
Автор ответа:
0
(2x-3)(2x+3)-x^2=12x-69-3x^2
4x^2-9-x^2-12x+69+3x^2=0
-12x+60=0
-12x=-60
x=-60(-12)
x=5
Ответ:x=5
4x^2-9-x^2-12x+69+3x^2=0
-12x+60=0
-12x=-60
x=-60(-12)
x=5
Ответ:x=5
Автор ответа:
0
а принцип какой ?
Похожие вопросы
Предмет: Українська література,
автор: Аноним
Предмет: География,
автор: Аноним
Предмет: Математика,
автор: FanikGGdrop
Предмет: Информатика,
автор: 1SKIN1
Предмет: Биология,
автор: rita22042001